226k views
1 vote
Solve the equation, using any method. Be sure to check for extraneous solutions.

2/(2x+6) - 2/x^2+5x+6= 3/(x+3)

1 Answer

2 votes

Answer: No real solution.

Explanation:


(2)/((2x+6))-(2)/(x^2+5x+6)=(3)/((x+3))

First solve
x^2+5x+6


(2)/((2x+6))-(2)/((x+3)(x+2))=(3)/((x+3))


([2(x+3)(x+2)]-[2(2x+6)])/((2x+6)(x+3)(x+2)) = (3)/((x+3))


([(2x+6)(x+2)]-(4x-12))/((2x+6)(x+3)(x+2)) = (3)/((x+3))


((2x^2+4x+6x+12)-(4x-12))/((2x+6)(x+3)(x+2)) = (3)/((x+3))


(2x^2+10x+12-4x+12)/((2x+6)(x+3)(x+2)) = (3)/((x+3))


(2x^2+6x+24)/((2x+6)(x+3)(x+2)) = (3)/((x+3))

Past this point, we can't solve
2x^2+6x+24 and obtain real values of x. Therefore, there are no real solutions.

User Vithani Chandresh
by
5.3k points